Unique Branding of Deaf Coffee: Opening a New Window to Introduce Deaf Friends Culture and BISINDO Sign Language - Irla Yulia; Diana Dogboyou (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2024)
Kopi Tuli represents a pioneering initiative in Indonesian coffee shop management, being one of the first establishments to be fully managed by Teman Tuli. In terms of communication, Teman Tuli utilises Indonesian Sign Language (BISINDO) as the primary language. This research project aims to analyse the branding strategy adopted by Kopi Tuli to increase awareness of Teman Tuli's existence and to evaluate the impact of Kopi Tuli's branding in introducing BISINDO sign language. The research was conducted using qualitative methods, comprising a literature review, observation and in-depth interviews. The results demonstrate that the branding strategy employed by Kopi Tuli is efficacious in increasing public awareness of Teman Tuli's existence and the introduction of BISINDO sign language. The branding strategy that has been deemed effective encompasses several pivotal elements that have collectively succeeded in attracting public attention. These include a transparent and distinctive brand positioning, a robust brand identity, the utilisation of social media as a pivotal campaign medium, an educational customer experience that enables direct acquisition of sign language skills, and an amplified public awareness of the Teman Tuli community.